Upaya Instruktur Tata Rias Pengantin dalam Mengembangkan Kemandirian Berwirausaha (Studi Pada Lembaga Kursus dan Pelatihan Yuwita) - Hanifa Qurrota Aini; Wiwin Herwina; Lilis Karwati (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to describe the efforts of bridal makeup instructors in fostering entrepreneurial independence among course and training participants. This study used a qualitative approach with descriptive methods. Subjects included instructors and students at bridal makeup course institutions. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study show that the instructors' efforts to foster entrepreneurial independence are carried out through: (1) strengthening the cognitive aspect by providing material on entrepreneurship, business management, and marketing strategies; (2) developing the affective aspect through fostering self-confidence, responsibility, discipline, and work ethic; and (3) improving the psychomotor aspect through direct practice of bridal makeup, customer service simulations, and portfolio preparation. A learning approach that integrates these three domains aligns with Benjamin Bloom's educational taxonomy theory, which emphasizes a balance between knowledge, attitudes, and skills. The study's conclusions indicate that the instructor's role is crucial in developing students' competencies and independence to start their own businesses. The recommendation of this research is the need for ongoing mentoring and strengthening of business networks to increase the entrepreneurial success of bridal makeup course graduates.